Anti-hiatus Tendency in Spanish: a Phonological Issue Involving Literary Precept and Normative Grammar - Alcoholado Feltstrom, Antonio (2020)
Hiatus resolution in Spanish speech by means of synaloephe and synaeresis has been studied by scholars from varied times and origins. This paper summarizes different authors’ evaluations from the disciplines of meters and grammar, notes the disagreement shown by normative grammar and literary preceptive about anti-hiatus pronunciation, and considers a possible reconciliation though the understanding of a phonological reality.